The work experiences and career development expectations of Chinese respiratory therapists: a descriptive qualitative study - Xu, Jianfeng; Cheng, Pengfei; Yu, Hangqing; Zhou, Niya; Lan, Meijuan (Frontiers in Medicine, 2024)
Background Respiratory therapists (RTs) play a vital role in healthcare, specializing in the treatment and management of heart and lung conditions, particularly during the COVID-19 pandemic. Despite the importance of RTs, little attention has been paid to RTs in the Chinese health system. This study aimed to understand and describe the work experiences and career development expectations of RTs in China. Methods This study utilized a qualitative research design and conducted semi-structured, in-depth, audio-recorded interviews with 16 RTs aged 28–40 years, purposively selected from six regions in mainland China from May to June 2024. Qualitative thematic content analysis was conducted to identify and group the themes that emerged from the discourse. Interviews were transcribed and analyzed using thematic analysis. Results Four key themes were identified: (1) “Complex Career Motivation” delves into the career trajectories and role adaptations of RTs; (2) “Positive Career Feedback” explores feelings of job satisfaction and career accomplishments; (3) “Uncertain Career Predicament” sheds light on the negative impact of multidimensional career challenges; (4) “Demand-Driven Future Outlook” reflects RTs’ urgent expectations for professional advancement. Conclusion The barriers and facilitators in the professional journey of Chinese RTs maintain a fragile balance, and the future development of the profession may determine whether they can persist in their careers. Healthcare managers and leaders should pay attention to the real needs of RTs, enhance their professional confidence, and adopt effective coping strategies to avoid the loss of human resources and promote the development of the professional team.